Effectiveness of Live Zoster Vaccine in Preventing Herpes Zoster Ophthalmicus (HZO). (4th October 2017) - Aukes, Laurie; Bartlett, Joan; Fireman, Bruce; Hansen, John; Lewis, Edwin; Earley, Elizabeth; Marks, Morgan; Saddier, Patricia; Klein, Nicola P
Abstract: Background: Herpes zoster ophthalmicus (HZO), caused by reactivation of varicella-zoster virus in or around the eye, can be severe and often results in care-seeking that may be less discretionary than for uncomplicated herpes zoster (HZ). We compared the vaccine effectiveness (VE) of live zoster vaccine against HZO with the VE against HZ overall. Methods: Kaiser Permanente Northern California (KPNC) members enter the ongoing cohort study when age-eligible for zoster vaccine starting in 2007. Incident HZ was defined as a new diagnosis of HZ with an antiviral prescription or a positive varicella viral test. Among those, an HZO case was defined as having an HZO diagnosis during an ophthalmology visit within 30 days of the initial HZ diagnosis. VE by age at vaccination and time since vaccination was estimated using Cox regression adjusted for age, race, sex and time-varying measures of healthcare use, comorbidities and immunocompromise status. Average VE over the first 5 years following vaccination was calculated as a weighted average of annual VE estimates. Results: During 2007–2014, 1.3 million individuals ≥50 years of age entered the study population and 29% were vaccinated. Among 48, 889 incident HZ cases, 2, 858 (6%) had HZO, 87% of whom were unvaccinated. For all ages combined, VE against HZO was 72% (95% CI, 64%-79%) in year 1, similar to 68% (95% CI, 65%-70%) against HZ. VE fell in years 2, 3, 4, and 5 to 47%, 45%, 42% and 27% for HZO and to 47%, 39%, 41% and 37% for HZ. For age groups 60 – 69 and 70 – 79, where we have the most data, initial VE and waning were similar for HZO and HZ. Numbers of HZO cases for 50–59 year olds were too small to evaluate at this time. Average VE against HZO over the first 5 years following vaccination was 52% (95% CI, 42%–60%) for ages 60–69, 51% (95% CI, 39%–61%) for ages 70-79, and 39% (95% CI, 14%-57%) for ages 80+; similarly, 5-year average VE against HZ was 49%, 46%, and 44% for these 3 age groups. Conclusion: VE against HZO was similar to VE against HZ regardless of age at vaccination or time since vaccination. Effectiveness of live zoster vaccine in preventing HZO was highest in year one with subsequent waning. Disclosures: E. Earley, Merck & Co.: Research Contractor, Salary; M. Marks, Merck and Co. Inc.: Employee, Restricted Stock and Salary; P. Saddier, Merck & Co., Inc.: Employee, Salary; N. P. Klein, GSK: Investigator, Grant recipient; sanofi pasteur: Investigator, Grant recipient; Merck & Co.: Investigator, Grant recipient; MedImmune: Investigator, Grant recipient; Protein Science: Investigator, Grant recipient Pfizer: Investigator, Grant recipient